2016
DOI: 10.1038/srep36451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetron sputtering parameters and stress state of W film precursors on WSe2 layer texture by rapid selenization

Abstract: Tungsten diselenide (WSe2) film was obtained by rapid selenization of magnetron sputtered tungsten (W) film. To prevent WSe2 film peeling off from the substrate during selenization, the W film was designed with a double-layer structure. The first layer was deposited at a high sputtering-gas pressure to form a loose structure, which can act as a buffer layer to release stresses caused by WSe2 growth. The second layer was deposited naturally on the first layer to react with selenium vapour in the next step. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…A previous study showed that increasing pressure decreased adatom energy and the atomic peening effect, which changed in-plane stress from compressive to tensile. [46,47] Similar trend was also observed in this experiment; it showed the transition from compressive to tensile stress (between ≈5 and 10 mTorr), and further increasing pressure resulted in higher tensile stress (Figure 6b). Also, decreasing the peening effect with increasing pressure decreased the film roughness, as shown in Table S1, Supporting Information.…”
Section: Structural and Chemical Propertiessupporting
confidence: 87%
“…A previous study showed that increasing pressure decreased adatom energy and the atomic peening effect, which changed in-plane stress from compressive to tensile. [46,47] Similar trend was also observed in this experiment; it showed the transition from compressive to tensile stress (between ≈5 and 10 mTorr), and further increasing pressure resulted in higher tensile stress (Figure 6b). Also, decreasing the peening effect with increasing pressure decreased the film roughness, as shown in Table S1, Supporting Information.…”
Section: Structural and Chemical Propertiessupporting
confidence: 87%
“…Recently, Hongchao Li et al. have demonstrated an environmentally friendly method to prepare WSe 2 films with different orientations on the non-conductive quartz glass [ 35 , 36 ]. Although WSe 2 thin films have many applications, such as p-n diodes [ 37 ], field-effect transistors [ 38 ], and logic devices [ 39 , 40 ], there are only a few reports that have proven its application in PV SCs so far [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the tensile strain is dominant, the film grows along the vertical direction of the substrate. 45,46 Here, the MoSe 2 @ZnO composite grew along the plane direction, and thus the compressive strain was greater than the tensile strain. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%